Exploring the Transformative Potential of Generative AI in Mechanical Engineering Education - Alghazo, Mohannad (2025)
A Master of Science thesis in Engineering Systems Management by Mohannad Alghazo entitled, “Exploring the Transformative Potential of Generative AI in Mechanical Engineering Education”, submitted in April 2025. Thesis advisor is Dr. Vian Ahmed and thesis co-advisor is Dr. Zied Bahroun. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).